The 2024 Declaration of Helsinki: Updates to the Ethics of Biomedical Research (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The 2024 update of the Declaration of Helsinki reflects the profound social, technological, and cultural changes that have occurred in recent decades and introduces significant innovations. Among the main updates is the shift from research “on” subjects to research “with” participants, who are now regarded as active agents and co-creators of the scientific process. The dimension of public health and community involvement is emphasized, even in intercultural contexts. Informed consent is redefined as “free” and “communicated,” based on clear and bidirectional interaction. The concept of risks and benefits is broadened to include psychosocial aspects and collective well-being. The notion of vulnerability is redefined, shifting from fixed categories to contextual factors and emphasizing inclusivity. Scientific integrity, data protection, and fair distribution of benefits become central elements. The document reaffirms the importance of ethics committees, equity in access, and transparency, outlining a vision of research that is increasingly inclusive, responsible, and grounded in respect for human dignity.
Keywords: Biomedical research; research ethics; consent; vulnerabilities; human dignity